DEVELOPMENT OF SOFTWARE MODULE FOR TRANSFORMERS COMPARATIVE CHARACTERISTICS CALCULATION TAKING INTO ACCOUNT COST-EFFECTIVENESS CONDITION - BUNIAK, OLEH; STASIV, ANDRII; OROBCHUK, BOGDAN; SUDOMYR, VALENTYN (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The development of the software module for calculating the transformers comparative characteristics by means of Windows Forms in C# programming language, intended for the implementation in the educational process of the Department of Electrical Engineering at Ternopil Ivan Puluj National Technical University is considered in this paper. Physically and morally outdated equipment in the electrical energy distribution links results in the increased technological costs. While analysing the reliable operation of electrical links of different voltage classes, the choice of power transformers, where the optimal criteria are capital and operating costs, technical characteristics and cost of electricity, annual operating time and electrical load schedule is of great importance This approach leads to the  increased complexity of calculations, constant changes in input data or their uncertainty, taking into account operation in overload modes and frequent outages during martial law. Therefore, it is important to develop software for quick calculation of transformers comparative characteristics. The proposed software module for calculating the transformers comparative characteristics has intuitive user interface, and high accuracy of calculations is ensured by the application of variables of the Double type for mathematical calculations, ensuring compatibility with most .NET mathematical libraries. One of the key functions of the program is the input data verification mechanism: the program module is highly resistant to user errors, and the program is built on the modular architecture and takes into account the possibility of future functionality updates minimizing the risk of incorrect results and increasing the reliability of calculations. The proposed software interface, which provides the choice of languages - the formation of input data for calculations in the software module in Ukrainian or English - is universal and can be integrated into any application with  localized interface to facilitate adaptation for different language groups.
Keywords: software module; transformer; program interface; program block